KORELASI ANTARA TINGKAT BERPIKIR KRITIS DENGAN KETERAMPILAN MEMBACA TEKS ARGUMENTASI BAHASA KOREA (Korelasional pada Mahasiswa Pendidikan Bahasa Korea Angkatan 2019) - Oktavianto, Dwi Bhakti (2022)
According to the PISA published in 2018, Indonesia ranks third lowest in terms of reading skills, indicating that reading skills among Indonesian learners are still quite inadequate. This is perhaps due to the fact that critical thinking abilities are still lacking in Indonesia as well. Previous literature has highlighted the interplay between reading skills and critical thinking abilities. A quantitative approach with a correlation design was used in this study. Sixty-two undergraduate students majoring in Korean language education were involved. Ennis' Theory was used to measure the critical thinking skills, while Tampubolon's Theory was used to measure the reading skills. The instruments used in this study included a critical thinking questionnaire and a reading test. The results of critical thinking skills are 3% "very high", 47% "high", 37% "low" and 11% "very low". The results of reading skills were 18 "very good", 24% "good", 29% "pretty good", 26% "less good", and 3% "very poor" in reading skills. Meanwhile, the students exhibited "fairly good" reading skills. Furthermore, the correlation between the two variables was found to be not strong enough, with a correlation coefficient 0.371. The effect of critical thinking abilities on the reading skills is 13.7%, with a coefficient of determination (R square) of 0.137. Based on the results, while critical thinking abilities were high, reading skills were not strong enough. It can be concluded that there is a weak correlation between the students' critical thinking abilities and their skills in reading Korean texts.